Despre bolile aparatului reproducător la reptile / About diseases of the reproductive tract in reptiles - Rudolf Kocsis; Romeo Teodor Cristina (Medicamentul Veterinar)
The attraction that reptiles exert on people cannot be explained too easily, but the fact that terrariums with various reptiles are increasingly present in our homes proves that the interest in these lives is certain, in the last decade being in great growth in our country. For this reason, the need for information on reptile needs, such as their multiplication, is of interest, not only to breeders, but especially to Romanian veterinarians, who do not yet benefit from an accumulated faculty base and, with the exception of Internet resources, a vast bibliographic base in Romanian language that can be called upon if needed. It is understandable then, why the specialized works on this subject are appreciated by those interested.